THE ENERGY MINIMIZATION AND THE COST REQUIREMENTS FOR THE POTATO RESIDUES REPROCESSING - Tarek FOUDA; F. A. AHMED; M. A. ALI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Field crop residues have become an urgent problem for the Egyptian farmer. Total cultivated area with this crop in Egypt, 189,000 hectare and the estimated quantity of haulm potatoes is about 1,575 Tg with an average of 8.3 Mg/hectare of haulm potato. Varied techniques were used for cutting waste of field crop, and the mechanical shredder residue for handling and use of these wastes were analyzed in order to reduce the size of the waste molecules to fit the various aspects of its uses. To optimize the operating parameters of the performance of farm residues it was used the cutting machine and it was established the minimum cost, power and energy requirements for produce animal feed raw materials from potato haulme. The performance of the machine units was measured under the following parameters four levels of drum speed of 25.13, 30.14, 35.17 and 40.19 m/s (1,000, 1,200, 1,400, and 1,600 rpm), three feed rates of 600, 800, 1000 kg/h, two number of knives on the cutting cylinder from (68 to 48). The performance of the cutting machine unite was taking into consideration machinery productivity, percentages of softness degree, cutting efficiency, fuel consumption, power, energy, and cost analysis. The optimum results and parameters for cutting machine untie when using drum speed 1,600 rpm, 1,000 kg /h feeding rates, and 68 number of knives.0.985 Mg/h productivity, 19,123 kW power, 19,414 kW.h/Mg energy, 6,046 l/h fuel consumption, 99 % cutting efficiency, 85% percentages of softness degree, and 9,850 l.E/h cost analysis.